Gestational Weight Gain and Pregnancy Outcomes among Nulliparous Women - Dude, Annie M.; Grobman, William; Haas, David; Mercer, Brian M.; Parry, Samuel; Silver, Robert M.; Wapner, Ronald; Wing, Deborah; Saade, George; Reddy, Uma; Iams, Jay; Kominiarek, Michelle A. (American Journal of Perinatology, 2019)
Objective To determine the association between total gestational weight gain and perinatal outcomes.Study Design Data from the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-To-Be (NuMoM2b) study were used. Total gestational weight gain was categorized as inadequate, adequate, or excessive based on the 2009 Institute of Medicine guidelines. Outcomes examined included hypertensive disorders of pregnancy, mode of delivery, shoulder dystocia, large for gestational age or small for-gestational age birth weight, and neonatal intensive care unit admission.Results Among 8,628 women, 1,666 (19.3%) had inadequate, 2,945 (34.1%) had adequate, and 4,017 (46.6%) had excessive gestational weight gain. Excessive gestational weight gain was associated with higher odds of hypertensive disorders (adjusted odds ratio [aOR] = 2.05, 95% confidence interval [CI]: 1.78–2.36) Cesarean delivery (aOR = 1.24, 95% CI: 1.09–1.41), and large for gestational age birth weight (aOR = 1.49, 95% CI: 1.23–1.80), but lower odds of small for gestational age birth weight (aOR = 0.59, 95% CI: 0.50–0.71). Conversely, inadequate gestational weight gain was associated with lower odds of hypertensive disorders (aOR = 0.75, 95% CI: 0.62–0.92), Cesarean delivery (aOR = 0.77, 95% CI: 0.65–0.92), and a large for gestational age birth weight (aOR = 0.72, 95% CI: 0.55–0.94), but higher odds of having a small for gestational age birth weight (aOR = 1.64, 95% CI: 1.37–1.96).Conclusion Both excessive and inadequate gestational weight gain are associated with adverse maternal and neonatal outcomes.
Keywords: gestational weight gain; cesarean delivery; small for gestational age birth weight; hypertensive disorders of pregnancy; large for gestational age birth weight